Pengaruh Model Problem Based Learning Terhadap Pemahaman Konsep Matematis Siswa Kelas V di UPT SDN 023 Pandau Jaya: Penelitian - Maya Rosa Indah; Siti Quratul Ain (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the effect of implementing the Problem Based Learning (PBL) model on the conceptual understanding of mathematics among fifth-grade students at UPT SDN 023 Pandau Jaya. The research employed a quantitative method with a posttest-only control group experimental design. The subjects consisted of 62 students, with class V-A assigned as the experimental group and class V-B as the control group, using a saturated sampling technique. The research instrument was a descriptive test that had been validated for validity, reliability, difficulty level, and discriminating power. Data were collected through documentation, observation, and testing, then analyzed using normality, homogeneity, and independent t-tests with the assistance of SPSS software. The results revealed that the posttest data were normally distributed and homogeneous, and there was a significant difference between the experimental and control groups with a significance value of 0.013 < 0.05. The mean posttest score of the experimental group was 15.13, which was higher than the control group’s score of 12.00. These findings indicate that the implementation of the Problem Based Learning model has a positive and more effective impact on improving students’ conceptual understanding of mathematics compared to conventional learning. Therefore, PBL can be recommended as an alternative instructional strategy that fosters active participation, collaboration, critical thinking, and conceptual understanding in mathematics learning at the elementary school level.